The Small Tourism Enterprise Operators’ Networking in Dealing with the Changing Business Environment - Akhmad Saufi; Yeldi Genadi; Agusdin Agusdin; Noel Scott (Universitas Pendidikan Ganesha, 2023)
The entrepreneur’s ability to networking is particularly critical when dealing with business turbulence, such as that affected by the COVID-19 pandemic. This study aims to analyze the STE operators manage their networks during the changing business environment affected by earthquake and COVID-19 pandemic in Lombok. Data was collected from twenty-one tourism entrepreneurs through semi-structured observations and interviews, and analyzed using content analysis. The study identifies three categories: parties involved in the network (tourism managers, tourism authorities, transport operators, destination communities, and tourists), linking methods (management network approach) and collaboration objectives (management network objectives). After the earthquake (when business turbulence was still not so intense), STE managers used direct physical contact, social media, and online partners to expand their networks, developing more cooperation (rather than collaboration) to create social exchange benefits. During the COVID-19 pandemic (when business turbulence was more intense), STE managers increased their use of social media to deepen their networks and focused on developing collaborations with a limited number of partners to reap the benefits of economic exchange. This study recommends local government intervention in improving the ability of STE management networks and building online-based networks.